2012
DOI: 10.7745/kjssf.2012.45.1.037
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ethylene Emission in Tomato (Lycopersicon esculentum Mill.) and Red Pepper (Capsicum annuum L.) Inoculated with ACC Deaminase Producing Methylobacterium spp.

Abstract: Improvement of plant growth by Methylotrophic bacteria can be influenced through alterations in growth modulating enzymes or hormones, especially by decreasing ethylene levels enzymatically by 1-aminocyclopropane-1-carboxylate (ACC) deaminase or by production of indole-3-acetic acid (IAA). In this study, the effect of seven strains of Methylobacterium on seedling ethylene emission of tomato and red pepper plants was evaluated under greenhouse condition. Ethylene emission was lowest in Methylobacterium oryzae C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Higher yields of rice and tomatoes have been reported following rhizospheric bioinoculation (Methylobacterium suomiense CBMB120) of crops (Poonguzhali et al, 2008) [13] . Another study confirmed that M. suomiense colonization resulted in improved yields from red pepper plants (Yim et al, 2012) [15] .…”
Section: Resultsmentioning
confidence: 82%
“…Higher yields of rice and tomatoes have been reported following rhizospheric bioinoculation (Methylobacterium suomiense CBMB120) of crops (Poonguzhali et al, 2008) [13] . Another study confirmed that M. suomiense colonization resulted in improved yields from red pepper plants (Yim et al, 2012) [15] .…”
Section: Resultsmentioning
confidence: 82%
“…165 Treatment of tomato and red pepper plants with Methylobacterium reduced the ethylene emission compared to control plants under greenhouse conditions also. 166 167 The transcriptional regulatory protein encoded by an open reading frame activates the acdS gene expression when ACC or 2-aminoisobutyrate is present as an inducer. It can regulate the transcription initiation process even in the absence of inducer molecule, when present excessively.…”
Section: Modulation Of Ethylene Levels In Plantsmentioning
confidence: 99%
“…However, a number of microorganisms present either in rhizosphere, phyllosphere or endosphere of the plants play crucial role in the sensing and transducing signal to the plants under stressed conditions in coordinated manner. It is well established that ethylene at lower concentration worked as signaling molecules and regulate several gene expression, transcription and translation lead to overall plant development ( Shaharoona et al, 2006 ; Yim et al, 2012 ; Bal et al, 2013 ; Ek-Ramos et al, 2019 ). In contrast, ethylene at higher concentration causes programme cell death, accelerating abscission, aging, inhibiting root elongation, senescence, leaf and fruit drop, etc.…”
Section: Introductionmentioning
confidence: 99%